2014
DOI: 10.1055/s-0034-1383550
|View full text |Cite
|
Sign up to set email alerts
|

Depressor Septi Nasi Modifications in Rhinoplasty: A Review of Anatomy and Surgical Techniques

Abstract: The anatomy of the nasal muscles contributes a social harmony in aesthetic rhinoplasty because these muscles coordinate the nose and the upper lip while smiling. Sometimes this coordination can be interrupted by the hyperactivity or variations of these muscles and may result as a deformity because of their dynamic functions and relations with the nose. In our daily practice, we usually perform the rhinoplasty without considering the dynamic functions. When the patients recover the muscle functions after operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…To prevent this from happening, it is essential to carefully examine the facial muscles and preoperative smile patterns. 11 Consistent with our study, in a review study on the effects of interventions on DSN muscle in rhinoplasty, Sinno et al showed that treatment of DSN muscle, which involves transection or displacement of the muscle, results in improved aesthetic outcomes in rhinoplasty. 12 Transection or displacement of this muscle improves the position of the nose tip and increases the smile line and enhances the beauty of the face.…”
Section: Discussionsupporting
confidence: 91%
“…To prevent this from happening, it is essential to carefully examine the facial muscles and preoperative smile patterns. 11 Consistent with our study, in a review study on the effects of interventions on DSN muscle in rhinoplasty, Sinno et al showed that treatment of DSN muscle, which involves transection or displacement of the muscle, results in improved aesthetic outcomes in rhinoplasty. 12 Transection or displacement of this muscle improves the position of the nose tip and increases the smile line and enhances the beauty of the face.…”
Section: Discussionsupporting
confidence: 91%
“…Some reports in the literature emphasize that the depressor septi nasi muscle should be cut during rhinoplasty to prevent the nasal tip from being pulled down, especially when laughing, and to prevent a decrease in nasolabial angle during the postoperative period [47,52]. However, these reports only took aesthetic results into consideration; moreover, RMM and EMG were not performed and the dynamic functions of the nose were not evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In such patients, it is appropriate to add surgical maneuvers that support the ENV. However, patients with thin skin, strong cartilage, a gummy smile, and nasal resistance within the normal limits should not undergo DCL repair [ 21 , 44 47 ]. We do not recommend DCL repair for patients with prominent nasal humps, especially those with a hypertrophic M. depressor septi nasi; nasal tip droop increases after hump resection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the procedure, the incisivus labii superioris is also cut at the labial vestibular incision; this enhances the result of the operation. Also in rhinoplasty [ 27 ], many surgeons transect the ILS to approach the depressor septi nasi muscle.…”
Section: Discussionmentioning
confidence: 99%